The Role of Coaches in Shaping the Character of Futsal Extracurricular Children at SD Muhammadiyah 1 Menganti - Alfarid, Hasraf (Journal of English Language and Education, 2025)
Character building is a crucial aspect of education, aiming to nurture a generation with integrity and a sense of responsibility. This study seeks to explore the role of futsal coaches in shaping students’ character through extracurricular activities at SD Muhammadiyah 1 Menganti. A qualitative descriptive approach was employed, with data collected through observation, interviews, and documentation. The research involved eight fourth and fifth-grade students actively participating in futsal, as well as the coach, principal, physical education teacher, and homeroom teachers as supporting informants. The findings reveal that the coach plays a role not only in teaching technical skills but also in guiding students' character development. During training, the coach instills values such as discipline, responsibility, teamwork, sportsmanship, and leadership through several approaches, including modeling positive behavior, consistently enforcing rules, using constructive communication, providing motivation tailored to each student’s character, and implementing a fair reward-and-consequence system. The impact of these approaches is evident in the students’ behavioral changes, both during training sessions and in their school and home environments. Students demonstrated improved discipline, self-confidence, teamwork skills, and a sense of responsibility. This success is further supported by the school’s commitment, effective communication with homeroom teachers, and active parental involvement. In conclusion, futsal can serve as an effective medium for character development when guided by a coach who fully understands their role. Futsal is not merely a sports activity but also a platform for imparting life values that foster students' holistic development—physically, socially, emotionally, and cognitively.